2017
DOI: 10.1080/15563650.2017.1319066
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional ingestion of Cordyceps fungus-infected cicada nymphs causing ibotenic acid poisoning in Southern Vietnam

Abstract: Cicada infected with Ophiocordyceps heteropoda in Vietnam contain ibotenic acid and are associated with a clinical syndrome consistent with its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 1 publication
2
19
2
Order By: Relevance
“…As Tricholoma and Amanita are related (taxonomic order Agaricales ), the biosynthesis of 6 should be similar to that of ibotenic acid, omitting the desaturation step. Further ibotenic acid‐ and tricholomic acid‐producing fungi have been proposed, ranging diverse taxa from Amantia species to Ustilago and Ophiocordyceps . The BGC reported here offers the opportunity to reassess the proposed producers on the genetic level, and thus verify or refute the hypothesis for further producers.…”
Section: Figurementioning
confidence: 76%
“…As Tricholoma and Amanita are related (taxonomic order Agaricales ), the biosynthesis of 6 should be similar to that of ibotenic acid, omitting the desaturation step. Further ibotenic acid‐ and tricholomic acid‐producing fungi have been proposed, ranging diverse taxa from Amantia species to Ustilago and Ophiocordyceps . The BGC reported here offers the opportunity to reassess the proposed producers on the genetic level, and thus verify or refute the hypothesis for further producers.…”
Section: Figurementioning
confidence: 76%
“…A number of Rhizopus species, including Rhizopus arrhizus (OTU4 and OTU462) and Rhizopus microsporus (OTU21 and OTU16) are opportunistic agents of human zygomycosis (fungal infection) and can be pathogenic. , Some Aspergillus species detected in the P1 stage, including Aspergillus flavus (OTU9) and Aspergillus fumigatus (OTU34), account for the majority of invasive mold infections. , Aspergillus intermedius (OTU2850 and OTU15), Aspergillus piperis (OTU4559), and other unidentified species of Aspergillus , whose functions are unknown, could be beneficial or potentially harmful to humans. Moreover, cicada flowers infected by Ophiocordyceps heteropoda have been found to cause ibotenic acid poisoning …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cicada flowers infected by Ophiocordyceps heteropoda have been found to cause ibotenic acid poisoning. 36 According to the results of high-throughput sequencing, the fungus Isaria cicadae dominated, and this was not affected by the region, compartment, or growth stage. The results indicated that the genetics of the species Isaria cicadae was relatively stable, and the formation of the fruiting bodies of cicada flowers was mainly caused by the fungus Isaria cicadae.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another patient ingested 15-16 cicada flowers; although he exhibited severe symptoms, he survived after 3 weeks of treatment. These observations suggest that there are individual differences in the doses of cicada flower poisoning (Doan et al, 2017). It is therefore crucial to establish more systematic, complete, and feasible pharmacological and toxicological research methods.…”
Section: Conclusion and Perspectivementioning
confidence: 99%